A Study of The Factors That Influence The Level of Consumer Satisfaction Towards The Use of Internet Banking - Vivi Vivi; Novita Novita (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
The development of Information and Communication Technology (ICT) has become an integral part of people’s life today. Various kinds of business and trade transactions have changed along with the advancement of ICT. One of the sectors that are influenced by the development in information and communication technology is banking. The presence of internet banking has brought more conveniences to the customers in conducting banking transactions anytime and anywhere. However, one of the challenges faced by banks in implementing online banking is the security factor. In addition, consumer satisfaction in conducting internet transactions can be influenced by factors of Technology Acceptance Model (TAM). Technology Acceptance Model (TAM) consists of perceived usefulness and perceived ease of use and excellent service from the provider. The purpose of this study is to determine whether security, perceived usefulness, perceived ease of use, and service quality havepositive influence on internet banking consumer satisfaction. Thetype of research is explanatory research type. The research variables consisting of independent variables are security factor, perceived usefulness, perceived ease of use, and service quality; meanwhile dependent variable is internet banking consumer satisfaction. The sampling technique used is accidental sampling method combined with snowball sampling method. Datais collected through questionnaires and interviews. Methods of data analysis used is Multiple Regression Analysis. The result shows that variables of  security, perceived usefulness, perceived ease of use, and service qualitysimultaneously influence internet banking consumer satisfaction. It shows that the four variables positively affect internet banking consumer satisfaction.